Depressive symptoms, conduct problems and alcohol use from age 13 to 19 in Norway: evidence from the MyLife longitudinal study - Geir Scott Brunborg; Lasse Bang; Jens Christoffer Skogen; Jasmina Burdzovic Andreas (BMC, 2024)
Abstract Background Even though mental health problems and alcohol use remain major challenges facing adolescents, our understanding of their developmental progressions primarily stems from cohorts coming 1 of age in the early 2000's. We aimed to examine and describe normative developmental trajectories of depression, conduct problems, and alcohol use across adolescent years among more recent cohorts of Norwegian youth born in the 21st century. Methods Multilevel mixed linear models for symptoms of depression and conduct disorder, and multilevel mixed logistic models for depressive disorder, conduct problems, any alcohol use, and risky drinking, were estimated with longitudinal data from a nationwide sample N = 3436 (55% girls) of Norwegian adolescents (mean age 14.3 [SD = 0.85] in 2017). We compared models with linear, quadratic, and cubic change with age, and models that tested moderation by sex and centrality (rural vs. urban communities). Results Average symptoms and the rate of depressive disorder increased sharply from age 13 to age 19, but both the initial levels and the rates of change were greater for girls than for boys. Average symptoms of conduct disorder and the rate of conduct problems increased in early adolescence and were greater for boys than girls. The rates of any alcohol use and risky drinking both increased sharply from age 14, but there were no notable sex differences either in the initial levels or rates of change over time. Adolescents from more rural communities had greater rates of any drinking in mid-adolescence, but there were no other effects of centrality. Conclusions This study provides a much-needed update concerning normative developmental trajectories of depression, conduct problems, and alcohol use among millennium cohorts. Consistent with prior studies, we observed significant increases in all outcomes across adolescence, with depression being both greater and more prevalent among girls and conduct problems being both greater and more prevalent among boys. Consistent with the emerging evidence, we observed no sex differences in alcohol use. Finally, there were no differences in the examined developmental trajectories as a function of centrality. These findings underscore the importance of early prevention and treatment of mental health and substance use problems.